Vaginal local therapy with Vagifem and Cicatridina in women after cervical and endometrial cancer treatment - Markowska, Janina; Mądry, Radosław; Fischer, Natalia (Menopause Review/Przegląd Menopauzalny, 2007)
The symptoms of radiation vaginitis and atrophic vaginitis in women after cervical and endometrial cancer treatment are both a difficult therapeutic problem. Local therapy with Vagifem and Cicatridina is an extremely effective treatment. Moreover, Vagifem therapy is not connected with a risk of cancer recurrence